Heritability of cooperative behavior in the trust game - Cesarini, David (National Academy of Sciences, 2008)
Although laboratory experiments document cooperative behavior in humans, little is known about the extent to which individual differences in cooperativeness result from genetic and environmental variation. In this article, we report the results of two independently conceived and executed studies of monozygotic and dizygotic twins, one in Sweden and one in the United States. The results from these studies suggest that humans are endowed with genetic variation that influences the decision to invest, and to reciprocate investment, in the classic trust game. Based on these findings, we urge social scientists to take seriously the idea that differences in peer and parental socialization are not the only forces that influence variation in cooperative behavior.